Sorghum headbugs and grain molds in West and Central Africa: II. Relationships between weather, headbug and mold damage on sorghum grains - Ratnadass, A.; Butler, D.R.; Marley, P.S.; Bandyopadhyay, Ranajit; Hess, D.E.; Akintayo, I. (Elsevier, 2003)
A regional Sorghum Head-Bug and Grain Mold Trial was conducted in 1996 and 1997 by WCASRN in, respectively, 15 and 13 research stations in ten west and central African countries. Empirical relationships between weather factors and head-bug damage on the one hand, and between weather factors and grain mold damage on the other hand, were examined using the “Window” computer program. No significant correlation was found between head-bug damage and those weather factors examined. In the case of grain mold, high relative humidity (RH) during early plant growth (5–40 days after sowing, DAS) on the one hand, and between end of flowering and harvest (65–125 DAS) on the other hand, were the most strongly correlated with mold incidence. The relationships between maximum RH and grain mold scores in the scatter diagrams were clearly non-linear, showing a marked increase in grain mold scores when the RH exceeded a threshold of about 95%. These results are discussed and future research directions are proposed.